STRATEGI PENGEMBANGAN KOMPETENSI DALAM UPAYA MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN PADA BENGKEL TEFA EXCELLENT 1TANGERANG - Abdul Rohman Al Goviqi; Denok Sunarsih; Agustina Mogi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. The acceleration of digital technology in the automotive industry demands high technical competency standards for the workforce to maintain organizational competitiveness. This study aims to analyze competency development strategies in an effort to increase employee work productivity at the TEFA Excellent 1 Workshop Tangerang, identify factors influencing the development process, and formulate an effective strategic design optimization. The urgency of this research lies in the importance of human resource adaptation to electrical and digital systems to mitigate operational hurdles that impact service efficiency.The research method used is descriptive qualitative with a case study approach. Data analysis was conducted systematically through Thematic Analysis following the six-phase protocol by Braun and Clarke, including data familiarization, coding, and definitive theme mapping. Data were collected through in-depth interviews with the owner, manager, and mechanics, and validated using source triangulation techniques and technical documentation to ensure the credibility and objectivity of field findings.The research results identified three main findings: (1) Competency development strategies are focused on strengthening mechanics’ digital literacy through the use of diagnostic tools (scanners) and specialization in electrical systems to accelerate the repair process; (2) The development process is influenced by internal factors such as technology adaptation motivation and external factors such as facility support and the culture of knowledge sharing (mentoring) among peers; and (3) Strategic optimization is achieved through the integration of technical expertise with educative communication competencies capable of accelerating customer decision-making. This study concludes that a significant increase in work productivity is determined by the HR’s ability to combine digital technical precision with service communication effectiveness. Strategic recommendations are directed toward the formalization of internal mentoring programs, regular updates of digital work tools, and strengthening industry certification coordination for all technical personnel. Keywords: Competency Strategy, Work Productivity, HR Management, Thematic Analysis, Automotive Industry.